2011
DOI: 10.5324/nje.v13i1.328
|View full text |Cite
|
Sign up to set email alerts
|

Dietary 'acid load' and self reported prevalence of hip fractures: A population based, cross sectional study

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…A high intake of fruits and vegetables should accordingly lower the acid load and reduce the urinary loss of calcium. In keeping with these considerations, we previously reported an association between hip fractures and a low intake of vegetables and fruits [22]. In the present study, we observed a positive association between BMD and intake of raw vegetables, but only with borderline significance.…”
Section: Discussionsupporting
confidence: 89%
“…A high intake of fruits and vegetables should accordingly lower the acid load and reduce the urinary loss of calcium. In keeping with these considerations, we previously reported an association between hip fractures and a low intake of vegetables and fruits [22]. In the present study, we observed a positive association between BMD and intake of raw vegetables, but only with borderline significance.…”
Section: Discussionsupporting
confidence: 89%